Problems of aggression in authoritarian leadership in large groups – psychoanalytic and group-analytic view - Veljković, Jasna J (Sociološki pregled, 2021)
Man is a being of a group that spends most of his life in groups distinguished by leadership, structure, type and organization. The human individual moves in the range between opposite tendencies: to belong to a group and be “invisible” in it or to be visible and become a leader. In this paper, our goal is theoretical research of the problems of sociodynamics and psychodynamics of aggression in large groups depending on the type of leadership. Research methods are: psychoanalytic and group-analytic methods. Our findings are that the occurrence of aggression in large groups is inevitable, but types and manifestations of aggression in large groups differ significantly, depending on the type of leadership in a large group (democratic or authoritarian), group cohesion, establishment or non-establishment of group identity and selection of group members.